Facilitatory Effects of Multi-Word Units in Lexical Processing and Word Learning: A Computational Investigation - Grimm, Robert; Cassani, Giovanni; Gillis, Steven; Daelemans, Walter (Frontiers in Psychology, 2017)
Previous studies have suggested that children and adults form cognitive representations of co-occurring word sequences. We propose (1) that the formation of such multi-word unit (MWU) representations precedes and facilitates the formation of single-word representations in children and thus benefits word learning, and (2) that MWU representations facilitate adult word recognition and thus benefit lexical processing. Using a modified version of an existing computational model (McCauley and Christiansen, 2014, The Mental Lexicon, 9, 419-436), we extract MWUs from a corpus of child-directed speech and a corpus of conversations among adults. We then correlate the number of MWUs within which each word appears with (1) age of first production and (2) adult reaction times on a word recognition task. In doing so, we take care to control for the effect of word frequency, as frequent words will naturally tend to occur in many MWUs. We also compare results to a baseline model which randomly groups words into sequences -- and find that MWUs have a unique facilitatory effect on both response variables, suggesting that they benefit word learning in children and word recognition in adults. The effect is strongest on age of first production, implying that MWUs are comparatively more important for word learning than for adult lexical processing. We discuss possible underlying mechanisms and formulate testable predictions.